Anterior, posterior, left anterior oblique, and geometric mean views in gastric emptying studies using a glucose solution - Phillips, W T; McMahan, C A; Lasher, J C; Blumhardt, M R; Schwartz, J G (European journal of nuclear medicine, 1995)
Previous research has shown that the single anterior view of the stomach overestimates the gastric half-emptying time of a solid meal compared to the geometric mean of the anterior and posterior views. Little research has been performed comparing the various views of gastric emptying of a glucose solution. After an overnight fast, 49 nondiabetic subjects were given a 450 ml solution containing 50 g of glucose and 200 microCi of technetium-99m sulfur colloid. Sequential 1-min anterior, posterior, and left anterior oblique views were obtained every 15 min. The mean percent solution remaining in the stomach for all three views differed from the geometric mean by 1.9% or less at all time points. Average gastric half-emptying times were: geometric mean, 62.7 +/- 3.3 min; anterior, 61.9 +/- 3.2 min; posterior, 63.5 +/- 3.5 min; and left anterior oblique, 61.6 +/- 3.3 min. These half-emptying times were not statistically different. For individual patients, differences between all three views and the geometric mean were not clinically important. Approximately 95% of all patients are expected to have gastric half-emptying times measured by any of the three single views within 17 min of the gastric half-emptying time obtained using the geometric mean. The imaging of gastric emptying using glucose solutions can be performed using a convenient single view which allows continuous dynamic imaging.